A Review of Empathy Education with Digital Means among College Students - Sun, Ruixia; Li, Jingyu (International Journal of Emerging Technologies in Learning (iJET), 2024)
The prevalence of the Internet and the development of digital technology have enabled people to communicate with each other easily and instantly. Yet the physical distance in virtual communication may inhibit intimacy and the expression of empathy towards each other. This paper has carried out a review study on the experiments of empathy training for college students, aimed at finding out the effective strategies for intervention activities. The review shows that educators incorporated various digital means into the curriculum design so that students may interact with each other online or with computer programs. In addition, self-reflection through writing and digital stories plays an essential role in the cultivation of empathy. Finally, the paper points out that further research should raise more concerns about the full-view assessment of empathy training results and the sustained development of empathic ability. The paper argues for the inclusion of more diversified subjects in the experiments.